2011
DOI: 10.1074/jbc.m110.194696
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the N5-proximal Asn on the Thermodynamic and Kinetic Stability of the Semiquinone Radical in Photolyase

Abstract: Flavoproteins can dramatically adjust the thermodynamics and kinetics of electron transfer at their flavin cofactor. A versatile regulatory tool is proton transfer. Here, we demonstrate the significance of proton-coupled electron transfer to redox tuning and semiquinone (sq) stability in photolyases (PLs) and cryptochromes (CRYs). These light-responsive proteins share homologous overall architectures and FAD-binding pockets, yet they have evolved divergent functions that include DNA repair, photomorphogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
1
34
2
1
Order By: Relevance
“…13 Damiani et al suggested that water molecules can enter the FAD pocket and form a PT pathway from the bulk water to FAD. 21 The formation of the FAD x state occurs in 3.3 ms in PL-N378D. Compared to this, spectroscopic studies in CRYI show that the photo-reduction of FAD ox occurs within 31 ps, the subsequent PT from Asp396 to FAD À occurs in 1.7 ms, while the backward transfer is two orders of magnitude slower (690 ms).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…13 Damiani et al suggested that water molecules can enter the FAD pocket and form a PT pathway from the bulk water to FAD. 21 The formation of the FAD x state occurs in 3.3 ms in PL-N378D. Compared to this, spectroscopic studies in CRYI show that the photo-reduction of FAD ox occurs within 31 ps, the subsequent PT from Asp396 to FAD À occurs in 1.7 ms, while the backward transfer is two orders of magnitude slower (690 ms).…”
Section: Introductionmentioning
confidence: 92%
“…19 In E. coli and A. nidulans PL, like in the entomic CRY, the mutation of Asn into Asp does not enable a PT to form FADH . 20,21 After photo-reduction, the E. coli PL Asn to Asp mutant (PL-N378D) shows a slightly different UV-vis absorption spectrum compared to the spectrum for FAD À . It is characteristic of the presence of a different FAD state, called FAD x , and the absence of FADH .…”
Section: Introductionmentioning
confidence: 99%
“…This unspecific pathway seems to be slow because, in photolyase from E. coli, protonation is not observed within hundreds of microseconds after anion radical formation (59). A kinetic barrier has been identified for the respective deprotonation step from the neutral radical to the oxidized state, which can be lowered by the N386D mutation close to flavin (60). A role of the aspartate as a proton shuttle in this photolyase mutant has accordingly been suggested.…”
Section: The Proton Transfer Pathway Is Different From Those In Othermentioning
confidence: 99%
“…The CRY-DASH proteins have Asn, not Asp, in the N5-proximal position, as shown with the published sequence alignment. 19 We also expect Asn to be proximal to N5 for VcCry1. From the literature, it appears plausible that the UV-p(dT) 10 molecule is acting to block proton transfer from the N5 position.…”
mentioning
confidence: 92%